Association between physical activity level and diabetes incidence among Chinese middle-aged and older adults: a cross-sectional study from the China health and retirement longitudinal study - Zhang, Yunqing; Meng, Fanhao; Fei, Xueyin; Wang, Ke; Wu, Yigao; Wang, Xueting (Frontiers in Public Health, 2024)
Background: It has been shown that diabetes is associated with insufficient physical activity among middle-aged and older adults, but the association between different physical activity levels (PAL) and diabetes incidence needs to be further explored.Objective: This study aims to explore the correlation and dose-response relationship between different PAL and the diabetes incidence in middle-aged and older adults.Utilizing data from the 2018 China Health and Retirement Longitudinal Study (CHARLS), this cross-sectional analysis included 17,226 middle-aged and older adults aged 45 and above. Binary logistic regression models and restricted cubic spline (RCS) were used to explore the correlation and dose-response relationship between different PAL and the incidence of diabetes in the total middleaged and elderly population as well as in subgroups. Sensitivity analyses were also performed to verify the robustness of the findings.In the entire study population, compared with the lowest PAL, participants in the third and fourth quartiles PAL saw diabetes incidence significantly reduced by 16% [OR=0.84, 95%CI (0.74, 0.95), (p=0.005)] and 33% [OR=0.67, 95%CI (0.58,0.77), (p<0.001], ), respectively (p for trend<0.001).In subgroup analyses, the fourth quartile PAL significantly reduced the diabetes incidence among females, individuals aged 60-69, and rural residents by 25% [OR=0.75,95%CI (0.62,0.91), (p=0.011)], 38% [OR=0.62,95%CI (0.49,0.77), (p< 0.001)] and 28% [OR=0.72,95%CI (0.6,0.86), (p<0.001)], respectively. For males, middle-aged (45-59 years), and urban residents, the third and fourth quartile PAL reduced diabetes incidence by 22%[OR=0.78,95%CI(0.64,0.95),(p=0.004] )and 41% [OR=0.59, 95%CI(0.48,0.73)p<0.001], 24% [OR=0.76,95%CI(0.62,0.94),(p=0.012)] and 39% [OR=0.61,95%CI(0.49,0.76),p<0.001], 21% [OR=0.79,95%CI(0.66,0.95),(p=0.013)] and 41% [OR=0.59,95%CI(0.46,0.75),p<0.001], respectively. When the fourth quartile PAL was reached, the diabetes incidence was significantly reduced in these populations by 41% (p<0.001), 39% (p<0.001), and 41% (p<0.001), respectively. There was a negative dose-response relationship between physical activity and diabetes incidence in specific Chinese middle-aged and elderly population. In addition, sensitivity analyses indicated the robustness of the findings. Conclusion: Higher PAL was associated with lower diabetes incidence in specific Chinese middleaged and elderly population. It is feasible to use physical activity to predict diabetes incidence in this demographic, and high PAL may be an effective means of preventing and controlling diabetes.